Identification of CCp5 and FNPA as Novel Non-canonical Members of the CCp Protein Family in Babesia bovis - Ozubek, Sezayi; Alzan, Heba F.; Bastos, Reginaldo G.; Laughery, Jacob M.; Suarez, Carlos E. (Frontiers Media Sa, 2022)
Bovine babesiosis, caused by Babesia bovis, is an economically significant tick-borne disease that imposes restrictions to livestock production worldwide. Current methods to control bovine babesiosis have severe limitations and novel approaches, including transmission-blocking vaccines, are needed. Members of the widely conserved CCp family are multidomain adhesion proteins containing LCCL motifs, which are differentially expressed on gametocytes of apicomplexans, including Babesia spp. and Plasmodium spp. While Plasmodium parasites contain 6 distinct CCp genes, only three members (CCp 1-3) were previously identified in B. bovis. In this study, we describe the identification and characterization of two novel non-canonical members of the CCp gene family in B. bovis, named CCp5 and FNPA. The genes were identified in silico by TBLASTN using P. falciparum CCp family domains as queries. Unlike CCp1-3, the B. bovis CCp5 and FNPA proteins lack the LCCL canonical domain but contain other typical multidomain adhesion motifs which are present in classical CCp proteins. In addition, the B. bovis CCp5 and FNPA are in synteny with known CCp genes in related apicomplexans. Sequence analysis of these two proteins demonstrated high sequence conservation among B. bovis different isolates. Transcription, immunoblot, and immunofluorescence analyses demonstrated expression of CCp5 and FNPA in blood and in vitro induced sexual stages of B. bovis. The FNPA, in contrast to CCp5, has a predicted transmembrane domain, suggesting that it might be expressed in the surface of sexual stage parasites. Altogether, finding of this study support FNPA as a possible target of a transmission-blocking vaccine against B. bovis.
Keywords: Babesia bovis; bovine babesiosis; sexual stages; transmission blocking vaccine; CCp protein family